PENGARUH BREATHING EXERCISE TERHADAP LEVEL FATIGUE PASIEN HEMODIALISIS DI RSPAD GATOT SUBROTO JAKARTA - Cahyu Septiwi (Jurnal Ilmiah Kesehatan Keperawatan, 2013)
The dependence of kidney failurepatients on dialysis machine, malnutrition and anemia can create fatigue.Fatigue can cause the malaise, sleepand emotional disturbances, decrease in concentration and the patient's ability to perform daily activities,and also reducethe quality of life. This study aimed to determine the influence of breathing exercise to the fatigue level of hemodialisyspatients in GatotSubroto Hospital of Jakarta. The study used aquasi-experimental research with pre and post test design,and purposive sampling technique with the inclusion criteria. The fatigue levelwas measured by the Fatigue Visual Numeric Scale. The results show that theaverage fatigue level of respondents before given breathing exercise is at 5.70with the standard deviation of 0.95. The average fatigue levelof after given the breathing exercise during 4weeks isat 3.80 with a standard deviation of 1.23. The difference in the mean level offatigue before and after the breathing exercise is 1.90. The results of pairedT test obtained p value of 0.000 that indicate that there are significantdifferences between the levels of fatigue before and after breathing exercise.Those results indicate that breathing exercises influence the fatigue level of hemodialisys patients.Nurses need to improve the quality of nursing care by implementing effectiveand efficient nursing interventions to solve the problem of hemodialysispatients and improve their quality of life.Keywords:fatigue level, breathing exercise, influence